Laser Cavitation Peening: A Review - Hitoshi Soyama; Yuka Iga (Applied Sciences, 2023)
During submerged laser peening using a pulsed laser, a bubble that behaves like cavitation is generated after laser ablation (LA). The bubble is referred to as laser cavitation (LC). The amplitude of the shockwave in water generated by LA is larger than that of LC; however, the impact passing through the target metal during LC is larger than that of LA. LC impact can be utilized for peening at optimized conditions. Thus, submerged laser peening is referred to as “laser cavitation peening”, as the peening method using the cavitation impact is known as “cavitation peening”. The impact induced by a hemispherical bubble is more aggressive than that of a spherical bubble with a microjet. Laser cavitation peening can improve the fatigue strength of metallic materials by producing work-hardening and introducing compressive residual stress. Three-dimensional additively manufactured metals (3D metals) such as titanium alloy are attractive materials for aviation components and medical implants; however, the fatigue strength of as-built components is nearly half of that of bulk metals, and this is an obstacle for the applications of 3D metals. In the present study, published research papers are reviewed to identify the key factors of laser cavitation peening, with additional visualization of LC and data. Then, improvements in the fatigue strength of metallic materials, including 3D metals treated by laser cavitation peening, are summarized.